Streben of the I as the Fundamental Form of Consciousness - Jurić, Andrija (Conatus - Journal of Philosophy, 2021)
This paper aims to show that Fichte’s concept of Streben or striving of the I is the necessary condition of finite or individual consciousness. The I posits itself absolutely, but in doing so it posits the not-I as well, therefore it posits itself absolutely as self-limiting I. If there was no limitation on the infinite striving of the I’s activity, then there would be no I, at least as we know it. Firstly, the paper emphasizes why this activity or striving needs to be infinite, and at the same time determined. Then, why is it necessary for theoretical self-consciousness, regarding the idea of Anstoss, divided self and absolute I. Finally, why is it also necessary for practical standpoint, considering the ideas of practical striving, tendency, longing, drive, and desire (both in individual striving towards self-coherence and social drive for intersubjectivity). It will be concluded that the I possesses a “dual nature” or divided character: it is finite, but it strives towards infinity. The tension arising from this contradiction should be the moving force of the I.